Influence of resistant varieties on the speed of propagation of simple epidemics in crops. (June 2017) - Gordillo, L.F.; Jordan, S.
Abstract: We determine the speeds of traveling wave fronts for simple epidemics in crops that contain a mixture of resistant and non-resistant hosts. For our model the wave speeds are found to be proportional to the fraction of resistant individuals. The conclusions are reached through the application of the linear conjecture, and verified by comparing the results with numerical solutions of the non-linear model.